Generalized erythematous and scaly plaques and papules: a rare case of Rosai-Dorfman disease accompanied by multiple myeloma - Shafiee, Anoosh (An Bras Dermatol, 2018)
A 75-year-old male presented with generalized erythematous, scaly plaques and painless lymphadenopathy. Rosai-Dorfman disease was suspected based on clinical manifestations and confirmed by histopathologic and immune reactivity studies performed on the biopsy obtained from the left supraclavicular lymph node. The patient was also diagnosed with multiple myeloma according to urine electrophoresis, serum light chain assay, and bone marrow biopsy, which were initially performed for evaluation of anemia. This report highlights the dermatological manifestations of Rosai-Dorfman disease with generalized painless lymphadenopathy.